Switzerland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper takes a close look at the proximate determinants and short-term dynamics of inflation in Switzerland. It identifies salient features of the inflation experience in Switzerland. The paper uses a wage-price model to gauge the sensitivity of inflation to the business cycle and the exchange rate. The findings suggest that underlying inflation of about 1 percent reflects a slightly higher rate for domestic goods and services and low increases in prices of imported goods.